2019
DOI: 10.7203/ciriec-e.97.12563
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatives and Social Capital: A Theoretically-Grounded Approach

Abstract: Social capital is widely regarded as a collective resource with positive effects on the economic performance of cooperatives. This conclusion is based on the implicit assumption that social interactions between cooperative members would inexorably lead to the development of networks, norms and trust. This paper challenges the validity of this assumption. Conceptualizing social capital as a resource of the individual, it is argued that the interactions between cooperative members may lead to the establishment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…On the other hand, various aspects of negative and antithetical social capital have been found to be relevant factors that might contribute to poor performance and dysfunction in cooperatives, and eventually lead to their failure and demise [11,78]. These include a reduced level of trust and loyalty among members, determined by factors such as the lack of transparency in decision-making processes and individualistic and opportunistic behaviors [78,79].…”
Section: Internal Dimension Of Cooperatives and Creation Of Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, various aspects of negative and antithetical social capital have been found to be relevant factors that might contribute to poor performance and dysfunction in cooperatives, and eventually lead to their failure and demise [11,78]. These include a reduced level of trust and loyalty among members, determined by factors such as the lack of transparency in decision-making processes and individualistic and opportunistic behaviors [78,79].…”
Section: Internal Dimension Of Cooperatives and Creation Of Social Capitalmentioning
confidence: 99%
“…There is also consensus on the importance of considering organizational plurality, assuming that different types of organizations (public, private for-profit, and nonprofit organizations, social enterprises, and other hybrid organizations) have specific characteristics that are interrelated with the nature of social capital in different ways [8,9]. Within this framework, cooperatives have received considerable attention in the academic literature because they are considered social capital-based organizations [10,11]. Some studies have analyzed how different internal mechanisms in cooperatives generate social capital within them, and how it is then extended to the community level [10].…”
Section: Introductionmentioning
confidence: 99%
“…Social capital and reputation can be either valued in their own right or as a means of obtaining other valued resources that are made available by memberships to the group (Spognardi, 2019). While in most cases it can be concluded that the level of innovation has a positive effect on reputation, Chun (2006) found that only when innovation is sustainable, it can be achieved positively with reputation; that is, RRI is needed.…”
Section: Jic 226mentioning
confidence: 99%
“…This has captured the attention of a significant number of studies from a microorganization perspective. It has been argued that its effects are positive but may vary significantly from case to case (Spognardi, 2019), allowing us to include the following hypothesis.…”
Section: Jic 226mentioning
confidence: 99%
“…One closely corresponds to Robert Putnam's contemporary notion of social capital. 60 According to the drafter of the statutes for credit cooperatives, the relation of mutual dependence upon which the cooperative was based, translated into a "greater and more intimate interpersonal interactions," which in turn contributed "the strengthening of bonds of fraternity and [to the development] of benevolent feelings." 61 The other argument pointed to the purported moralizing power of private property.…”
Section: The Reaction Of the Parliamentmentioning
confidence: 99%